Open science is good science, so what's getting in the way? - Cyran, Laura K. (University of Toronto Medical Journal, 2022)
The replication crisis in psychology has revealed that questionable research practices may have undermined the credibility of previously published research. This has led to meta-scientific efforts dedicated to improving research integrity and credibility by prioritizing transparency and reproducibility of research. This can be done through the use of open science practices, such as study preregistration, open data sharing, open source/code sharing, open-source publishing, and prioritizing replication studies. Many scientists agree that open science practices align with their scientific values, yet they are not currently standard practice. It is proposed that incentive structures that reduce the likelihood of adopting open science practices play a role in scientists' decision-making as they design, conduct, analyze, and disseminate results from their research. In order to improve the quality of the scientific record, systemic paradigm shift must occur at each step along the way.